2020
DOI: 10.1039/d0cc01605e
|View full text |Cite
|
Sign up to set email alerts
|

Electrical tension-triggered conversion of anaerobic to aerobic respiration of Shewanella putrefaciens CN32 cells while promoting biofilm growth in microbial fuel cells

Abstract: A global gene expression analysis of S. putrefaciens CN32 cells within the diffusion layer of the microbial fuel cell anode with surface controlled reaction reveals an electrical tension-triggered conversion of anaerobic to aerobic respiration, which represents the nature of the biofilm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…8 It is to be noted that Shewanella putrefaciens was recently found to promote bidirectional extracellular electron transfer 29 and the growth of biofilm in MFCs. 30 On the other hand, an MFC that used Shewanella oneidensis MR-1 cultured in bamboofermented effluent has shown agreeable performance results with this work. 31 It was observed that the generated power from a Shewanella oneidensis MR-1 in an MFC can be enhanced with the adoption of ferric iron as reported by Wu et al 32 While the COD removal of an MFC, which used Shewanella oneidensis MR-1, can be improved by the implementation of a biomass-based anodic substrate, as shown by Baniasadi and Vahabzadeh.…”
Section: Experiments Verification and Mathematical Modelsupporting
confidence: 81%
“…8 It is to be noted that Shewanella putrefaciens was recently found to promote bidirectional extracellular electron transfer 29 and the growth of biofilm in MFCs. 30 On the other hand, an MFC that used Shewanella oneidensis MR-1 cultured in bamboofermented effluent has shown agreeable performance results with this work. 31 It was observed that the generated power from a Shewanella oneidensis MR-1 in an MFC can be enhanced with the adoption of ferric iron as reported by Wu et al 32 While the COD removal of an MFC, which used Shewanella oneidensis MR-1, can be improved by the implementation of a biomass-based anodic substrate, as shown by Baniasadi and Vahabzadeh.…”
Section: Experiments Verification and Mathematical Modelsupporting
confidence: 81%
“…The core genes related to the iron transport system that was reported in our previous work (He et al, 2020) include heme ABC transporter ATP-binding protein (hABCATP), hemin ABC transporter substrate-binding protein (hemeABC), energy transducer TonB (enTonB), and iron ABC transporter permease (iron ABC). Additionally, the target genes encompass both the core genes related to the iron transport system and the outer membrane electron transfer-related genes (mtrA, mtrB, mtrC, undA, feoA, feoB) of S. putrefaciens CN32 (Wu et al, 2018b;Zou et al, 2019).…”
Section: Target Genes Selections and Validation Of Target Genes By Re...mentioning
confidence: 99%
“…(24) Next to the anode, there was the presence of S. putrefaciens CN32 cells and its global gene expression showed that due to anaerobic respiration, there was increased production of flavin and synthesis of cytochrome C. This results in electron transfer in the long-distance and also helps in biofilm formation. (40) There had been numerous microbial fuel cells that are applied for the treatment of wastewater, but due to the appearance of the nitrogen, induces unreliability in the performance by varying contents of the working biofilms. (41) The ShewanellaOneidensis MR-1 grew for over fifty days and lactate was not oxidized fully into acetate which had the huge recovery of electrons gained as electricity.…”
Section: Microbial Fuel Cell (Mfc)mentioning
confidence: 99%